The effect of kegels exercises on sexual function in elderly in the east Jakarta region - Halim, Suryani Hartati; Laela, Sri (Jurnal Keperawatan, 2024)
Introduction: Elderly people experience a decline in the function of their reproductive organs, which will affect intimate relationships with their partners, thus having an impact on physiological problems regarding sexual needs, so they are expected to be able to adapt to changes by improving their sexual function by doing Kegel exercises. Objectives: to determine the effect of Kegels exercises on sexual function in the elderly in the East Jakarta area. Methods: The research uses a quasi-experimental design with a pre-post test design without a control group, namely observations carried out before treatment and after treatment without using a control group, with a total of 27 respondents starting from May to August 2023 using the 19-item FSFI questionnaire. Results: The results showed that sexual scores increased by an average of 2 after Kegel exercises were carried out: sexual desire was 2, sexual arousal was 2.63, lubrication was 1.37, organism was 1, sexual satisfaction was 1.70, pain decreased by 1.19, p value = 0.000, and FSI score ≤ 26.55 for 21 people (77.8%) who did not experience sexual dysfunction. Conclusion: Sexual function will increase if you do light exercise such as gymnastics, namely Kegels exercises. This can also reduce sexual dysfunction.